Primary Plasmacytoma of the Kidney - R. A. J. Spence; A. Thwaini; D. M. O'Rourke (Case Reports in Urology)
Primary renal plasmacytomas are an extremely rare clinical condition. Their management is particularly challenging due to the paucity of evidence, with only just over a dozen previously reported cases. We report a case of a primary extramedullary plasmacytoma of the kidney and performed a review of the literature. The case is presented as a learning point that it is imperative to keep plasmacytic tumours in mind and to include them in the differential diagnosis of anaplastic tumours, even in unusual locations, such as the kidney.